Two's Company, Three's a Crowd? Maternal and Paternal Talk About Their Infant Differs in Associations With Wellbeing, Couple Relationship Quality, and Caregiving Sensitivity - Foley, Sarah; Álvarez, Carolina; McCarthy, Jade; Hughes, Claire (Frontiers in Psychiatry, 2020)
Problems of depression and anxiety are common in early parenthood and adversely affect parenting quality (Galbally & Lewis, 2017). Rumination is closely linked to poor wellbeing (Takano & Tanno, 2009), suggesting that self-focus may be one mediator of the association between wellbeing and caregiving (e.g., Humphreys, King, Choi, & Gotlib, 2018). Framed within an international study of first-time mothers and fathers (Hughes, Devine, Mesman, & Blair, 2019), the current study included 396 British mothers and fathers (in 198 heterosexual cohabiting couple relationships) of first-born 4-month-old infants. Parents reported on their symptoms of depression, anxiety and satisfaction in their couple relationship. Five-minute speech samples were transcribed and coded for parents’ pronoun use (i.e., ‘I’ and either infant- or partner-inclusive use of ‘We’), whilst observations in the Still-Face paradigm were coded for parental sensitivity to infants’ cues. Our first goal was to test whether new parents’ self-focus was associated with wellbeing and couple relationship quality. We also examined whether (i) self-focus mediated the expected association between wellbeing and caregiving sensitivity and (ii) couple relationship quality moderated the expected association between self-focus and caregiver sensitivity. Finally, we compared results for mothers and fathers. Our results illustrate gender-specific associations. First, although mean levels of self-focus and partner-inclusive talk were similar for mothers and fathers, infant-inclusive use of the ‘we’ pronoun was higher in mothers than fathers. Second, self-focus was unrelated to either mothers’ or fathers’ wellbeing, but was associated with fathers’ report of reduced couple relationship quality. In addition, poor perinatal wellbeing was associated with reduced partner-inclusive talk for fathers, but with reduced use of infant-inclusive talk for mothers. Third, mediation models suggest that reduced infant-inclusive talk underpins the association between poor wellbeing and reduced sensitivity in mothers, but not fathers. Fourth, in the context of good couple relationship quality, mothers’ elevated partner-inclusive talk was associated with reduced caregiving sensitivity. These findings are discussed in terms of their implications for interventions to support new mothers and fathers, who may benefit from distinct strategies to foster attention to their developing infant.